Intimal thickening of jugular and femoral veins vs arteries in the rabbit following investment - Funaki, C; Naito, M; Hayashi, T; Kuzuya, M; Asai, K; Kuzuya, F (Angiology, 1990)
The authors induced intimal thickening in the jugular and femoral veins and in the common carotid and femoral arteries of rabbits by placement of a polyethylene tube cuff. The comparative effects on the intima were studied by light and electron microscopy. Even in the veins, thickening resulted from the migration of medial smooth muscle cells into the intima with subsequent proliferation. Thickening in the arteries consisted of tightly packed smooth muscle cells and a few elastic fibers, whereas that in the veins was characterized by an abundance of collagen fibers, layers of smooth muscle cells, and a few elastic fibers. Capillaries were often observed in the thickened intima of the veins but not of the arteries.